Job satisfaction and its associated factors among medical and health officers in Terengganu - Nafsun, Aziemah (2024)
Introduction: Understanding job satisfaction is crucial for enhancing higher levels of engagement, dedication, and commitment to work, which will improve the overall quality of healthcare services provided. Thus, this study investigated job satisfaction and its associated factors among medical and health officers working in primary healthcare in Terengganu. Methodology: In this cross-sectional study, medical and health officers from all eight district health offices and state health departments of Terengganu were randomly and proportionately selected as participants. These participants had worked for at least three months in the district health offices and state health departments of Terengganu. The study used the Malay version of the Psychosocial Aspect of Work Questionnaire (PAW-M) which was self-administered using a Google form link. It consists of 15 items that measure three aspects of work: job satisfaction, social support, and the mental stress of work, and scored using a 5-point Likert scale. The data was analyzed using SPSS version 27, and linear regression analyses were applied to identify the factors that are associated with job satisfaction. Results: A total of 200 medical and health officers participated in the study. The study indicates that medical and health officers had a mean (SD) job satisfaction score of 26.41 (4.7). The mean age of the participants was 35.45 (4.80), the mean of social support was 16.67 (2.32) and the mean of mental stress was 17.29 (2.07). The study identifies that satisfied with income (95% CI: 0.118, 2.317, p=0.030), permanent employment status (95% CI: 0.104, 3.403, p=0.037) and social support score (95% CI: 0.979, 1.432, p<0.001) as the significant associated factors for job satisfaction among study participants. Conclusion: The study found that the mean job satisfaction score was 26.1, associated with satisfaction of income, permanent employment status, and social support score. Addressing these factors will boost job satisfaction among medical and health officers and thus improve the quality of healthcare services.